(untitled) (De Signos y Sentidos, 2025)
This article presents a synthesis of the circuit of extension activities (involving undergraduate and graduate students, in-service teachers, and basic education students), research (ranging from scientific initiation to graduate studies), and teaching (both at the undergraduate level and in schools), which are interconnected and fostered within the framework of the Ateliê de Textos program at the Federal University of Santa Maria, in partnership with public schools in southern Brazil. The theoretical and methodological foundations of these practices draw on Systemic Functional Linguistics (Halliday, 1985; Halliday & Matthiessen, 2014), Genre Pedagogy (Rose & Martin, 2012), and the Sociorhetorical approach (Bazerman, 2006). The extension–research–teaching circuit developed through this program has contributed to the professional growth of pre-service and in-service teachers, who, as members of a multidisciplinary team, refine their approaches to analyzing texts produced in schools, intervene more effectively in learning processes, and engage in opportunities for interaction through texts beyond the classroom. In this way, participants experience all stages of the textual production process, from the study of the focal genre through detailed reading and linguistic analysis activities, to the writing, rewriting, and dissemination of the final versions of new texts produced by students in basic education.